Optimization for header parameters of rape combine harvester - WU Wenjie; WU Chongyou (浙江大学学报. 农业与生命科学版, 2018)
Header losses are the most serious part of grain loss which affects the quality and efficiency of rapeseed harvesting operations. In order to solve this problem, we chose the reel’s horizontal position, reel’s vertical position and reel’s rotation speed as the main parameters, and took the header loss rate as the main objective. At the same time, we used the total feeding amount as an auxiliary target considering the harvester’s operation efficiency. First, single-factor test was performed on the three main parameters, and the effects of different factors on the loss rate and feed amount were analyzed. On the basis of single factor, a response surface test was conducted on the three main parameters according to the Box-Benhnken center combination design theory. Then, a regression model was established to determine the factors affecting significance. The experimental results showed that the loss rate was affected by the reel’s horizontal position, reel’s vertical position and reel’s rotation speed, while the total feeding amount was only affected by the reel’s rotation speed. The result of response surface experiment was consistent with the results of single factor experiment; the significant order of influence is reel’s vertical position, reel’s rotation speed and reel’s horizontal position through the analysis of impact effects. The optimum working parameter combination of the rapeseed harvester’s header with high efficiency and low loss rate as constraints was that the horizontal position of the reel was 50 mm, the vertical position of the reel was 1 056 mm, and the rotation speed of the reel was 30 r/min. Under the optimized conditions, the header loss rate was 0.97%, the feed amount was 8.35 kg/s, and the experimental value was 1.01% for the header loss rate, 8.48 kg/s for the feed amount with the relative error of less than 5%. The above results can provide a reference for optimization design of the header structure of rape combine harvester and optimization of operating parameters.